The Role of Health-Conscious Decisions in Food Consumption - Erzsébet Peter; Nikoletta Kaszás; Kornél Németh (DETUROPE)
The Ministry of Rural Development in Hungary has set the goal of restoring the competitiveness of the domestic food industry among many others. They would like to contribute to the stable financing by facilitating borrowing loans as well as export financing the enterprises in the food industry. For the period between 2014 and 2020, 500 billion HUF subsidies have been allocated for the technical and technological modernization of businesses, for the increase of input efficiency as well as for research and development and trainings and consultancy. In order to do so it is essential to encourage the demand for Hungarian food products besides insuring workforce with up-to-date expertise and the supportive economic environment. The research mentions consumption figures based on food balances where the balances calculated for various food groups include food products and beverages converted into ingredients. The development of food consumption is negatively affected by the economic recession, the weather influencing cultivation significantly as well as the fall in consumption from private farming. Enterprises put great emphasis on prevention and on the good physical and mental condition of their colleagues with such organization of work that focuses on health since work can be more efficient by this means. The quality of the work environment influences the health condition both directly and indirectly. In case of micro- and small enterprises cafeteria plans as well as the visible elements of corporate culture are much more revealed thus contributing to more health-conscious food consumption in Zala County. In addition to the agricultural support of the sale of domestic food products, the government could stimulate the manufacturing of healthy products of local small-scale producers indirectly by reducing VAT for instance.